(untitled) (Papeles, 2024)
Introduction: Is it possible to improve chemistry learning in university students by implementing knowledge integration materials with contextualized examples of medications? A large part of the theoretical content included in the General Chemistry syllabus can be addressed through contextualized examples. This promotes student involvement and interest in chemical-pharmaceutical concepts. Methodology: This is a mixed study in which educational materials are designed and implemented that incorporate the topics of solutions and acid-base chemical balance with contextualized examples of drugs and medications. The evaluation instruments consisted of questionnaires with open and closed questions with which ideas, concepts and procedures were collected from the students. Results and discussion: The learning results show that for Dilutions and Solutions there is an increase from 70 to 90% in the understanding of the theoretical concepts, but in related exercises the students present generalized difficulty. For the concepts related to Acid-Base Chemical Equilibrium, progress in understanding was evident with a 15% increase in where students identified the ionized species. Conclusions: As evidence of this research work, the use of contextualized examples allows adaptation to diverse educational environments since the specific needs of students are evident. This teaching suggestion illustrates how the use of contextually adapted exercises, such as those related to medications, can enrich the teaching of chemistry.